2020
DOI: 10.1121/10.0001952
|View full text |Cite
|
Sign up to set email alerts
|

Exploring design variations of the Titian Stradivari violin using a finite element model

Abstract: Because violins are traditionally hand-crafted using wood, each one is unique. This makes the design of repeatable experiments studying some aspects of its dynamic behavior unfeasible. To tackle this problem, an adjustable finite element (FE) model of a violin soundbox using the geometry and behavior of the “Titian” Stradivari was developed in this paper. The model is parametric, so its design and material properties can be varied for before/after comparisons in both the frequency and time domains. Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…Inspecting matrix P in the same figure, it can be noticed that the addition of the f-holes has a relevant impact on the amplitudes, in particular for peaks 1, 4 and 5. The sensitivity of FRFs to f-holes detected in the feature vectors agrees with [16], where a systemic analysis of these components was performed.…”
Section: Fea Simulations Of Stradivarius' Titiansupporting
confidence: 70%
See 2 more Smart Citations
“…Inspecting matrix P in the same figure, it can be noticed that the addition of the f-holes has a relevant impact on the amplitudes, in particular for peaks 1, 4 and 5. The sensitivity of FRFs to f-holes detected in the feature vectors agrees with [16], where a systemic analysis of these components was performed.…”
Section: Fea Simulations Of Stradivarius' Titiansupporting
confidence: 70%
“…To show the effectiveness of the feature-based representations presented in Section 2, two case studies are proposed. The first dataset is composed by bridge admittances predicted by means of Finite Element Analysis (FEA) using the Stradivarius' Titian violin as reference [16]. The second application analyzes similarities between experimental acquisitions taken on a set of contemporary violins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the response frequency increases when the height of the arch, the thickness of the front plate, the prestress of the front plate or the contact stiffness of the sound post increases. In a recent noteworthy study [72], the design variations of a Titian Stradivari violin were explored via FEM modeling. The model is parametric; hence, its design and material properties varied in both the frequency and time domains.…”
Section: Bowed Musical Instrumentsmentioning
confidence: 99%
“…In the state of the art, the most used simulation method to study real musical instruments is the Finite Element Method (FEM) [5], which is a very powerful but also time-consuming process. The main advantage of our approach lies in the fact that, using neural networks, we can compute and optimize the vibrational response of a violin top plate in few seconds, taking much less time than with a FEM analysis.…”
Section: Introductionmentioning
confidence: 99%